1959
DOI: 10.1287/mnsc.5.3.250
|View full text |Cite
|
Sign up to set email alerts
|

The Systems Research Laboratory's Air Defense Experiments

Abstract: The "off-the-top" findings of the air-defense experiments conducted in RAND's Systems Research Laboratory between 1952 and 1954 were the training principles that are the basis of the system training program being implemented by the System Development Corporation. There are, however, other theoretical and methodological implications. The desired performance of complex systems can be realized only through designing and managing them for operational flexibility. This can be done by harnessing the learning ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

1967
1967
2015
2015

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 6 publications
0
16
0
2
Order By: Relevance
“…Thus, from the original studies focused on organizational learning (Argyris, 1976;Cangelosi & Dill, 1965;Chapman, Kennedy, Newell, & Biel, 1959;Cyert & March, 1963;Hirschman & Lindblom, 1962;March & Olsen, 1975) there is a very rapidly growing interest from a diverse variety of academic perspectives on this subject (Bontis, Crossan, & Hulland, 2002;Crossan, Kane, & White, 1999;Jones & Hendry, 1994;March, 1991;Romme & Dillen, 1997;Senge, 1990;Stata, 1989). The continuing popularity of this paradigm has resulted in two main perspectives: 1) Learning organizations can be seen as "…organizations where people continually expand their capacity to create the results they truly desire, where new and expansive patterns of thinking are nurtured, where collective aspiration is set free, and where people are continually learning to see the whole together" (Senge, 1990).…”
Section: Organizational Learningmentioning
confidence: 99%
“…Thus, from the original studies focused on organizational learning (Argyris, 1976;Cangelosi & Dill, 1965;Chapman, Kennedy, Newell, & Biel, 1959;Cyert & March, 1963;Hirschman & Lindblom, 1962;March & Olsen, 1975) there is a very rapidly growing interest from a diverse variety of academic perspectives on this subject (Bontis, Crossan, & Hulland, 2002;Crossan, Kane, & White, 1999;Jones & Hendry, 1994;March, 1991;Romme & Dillen, 1997;Senge, 1990;Stata, 1989). The continuing popularity of this paradigm has resulted in two main perspectives: 1) Learning organizations can be seen as "…organizations where people continually expand their capacity to create the results they truly desire, where new and expansive patterns of thinking are nurtured, where collective aspiration is set free, and where people are continually learning to see the whole together" (Senge, 1990).…”
Section: Organizational Learningmentioning
confidence: 99%
“…Research reported by Chapman, Kennedy, Newell, and Biel (1959) and by Finley, Rheinlander, Thompson, and Sullivan (1971) supports the position that the effectiveness of larger military units is in part determined by subordinate team performance. However, conflicting results have been obtained on the factor.…”
Section: )mentioning
confidence: 89%
“…James Driskell and Beckett Olmstead (1989, 53) Laboratory in a room behind a Santa Monica billiard hall and brought in a few more psychologists and coders. In their first RAND research memorandum in January 1952, the design team explained, "(t)he Systems Research Laboratory will be studying particular kinds of models 8 The early history of the Systems Research Laboratory is discussed in Chapman and Kennedy 1955;Chapman, Kennedy, et al 1959;Baum 1981;Ware 2008, 94-98. In Von Neumman, Morganstern, andthe Creation of Game Theory, Robert Leonard (2010), examines the relationship between the SRL and the rest of the RAND mathematics department and stresses Kennedy's point that the limits of game theory and mathematical modeling made empirical research through simulation a necessity.…”
Section: Systems Research Laboratory 1951-1956mentioning
confidence: 99%